The Effect of Tax Knowledge, Application of E-Billing System and Understanding of The Tri Nga Teachings - Sri Lestari YP; Leo Frandika Putra (Universitas Muhammadiyah Makassar, 2022)
This study aims to examine the effect of knowledge of taxation, application of the e-billing system, and understanding of the teachings of tri nga (ngerti, ngroso, and nglakoni) on individual taxpayer compliance. This study uses a quantitative approach. The data used is prime data with the method of distributing questionnaires. There are three independent variables in this study, namely (PP) knowledge of taxation, (peB) application of the e-billing system, and (pTN) understanding of the teachings of tri nga (ngerti, ngroso, and nglakoni). The dependent variable (KWP) in this study is individual taxpayer compliance. The population used in this study is an individual taxpayer who is in the area of the Yogyakarta Pratama Tax Service Office. Sampling using convenience sampling in order to obtain a sample of 100 individual taxpayers at KPP Pratama Yogyakarta. Data analysis techniques in this study are descriptive statistics, classical assumption test and multiple linear regression. Data from the questionnaire was carried out using Microsoft Excel 2016 Software and processed using the IBM SPSS Statistics 20 program. The results showed that tax knowledge had a positive and significant effect on individual taxpayer compliance as indicated by the tcount value greater than the ttable value, which was (6,798>1,984) and the significant value of 0.000 is smaller than the 5% significance level (α=0.05). The implementation of the e-billing system has a positive and significant effect on individual taxpayer compliance, which is equal to (2.167>1.984) and a significant value of 0.033. Understanding the teachings of tri nga (ngerti, ngroso, and nglakoni) has a positive and significant effect on individual taxpayer compliance, which is equal to (2.504>1.984) and a significant value of 0.014